Ginsenoside Rg3 stereoisomers differentially inhibit vascular smooth muscle cell proliferation and migration in diabetic atherosclerosis. Issue 6 (22nd March 2018) - Guo, Mengqi; Guo, Guanlun; Xiao, Jie; Sheng, Xi; Zhang, Xinyu; Tie, Yuanyuan; Cheng, Yuen‐Kit; Ji, Xiaoping
Abstract: Ginsenoside 20(R/S)‐Rg3, as a natural peroxisome proliferator‐activated receptor gamma (PPARγ) ligand, has been reported to exhibit differential biological effects. It is of great interest to understand the stereochemical selectivity of 20(R/S)‐Rg3 and explore whether differential PPARγ activation by Rg3 stereoisomers, if it exists, could lead to differential physiological outcome and therapeutic effects in diabetic atherosclerosis. Here, we investigated the binding modes of 20(R/S)‐Rg3 stereoisomers in the PPARγ ligand‐binding domain (PPARγ‐LBD) using molecular modelling and their effects on smooth muscle cell proliferation and migration induced by advanced glycation end products (AGEs). The results revealed that 20(S)‐Rg3 exhibited stronger antiproliferative and antimigratory effects due to stronger PPARγ activation. To validate the in vitro results, we used a mice model with diabetic atherosclerosis and obtained that 20(S)‐Rg3 markedly reduced the plaque size secondary to reducing the proliferation and migration of VSMCs, while the plaques were more stable due to improvements in other plaque compositions. The results shed light on the structural difference between Rg3 stereoisomers that can lead to significant differential physiological outcome, and the (S)‐isomer seems to be the more potent isomer to be developed as a promising drug for diabetic atherosclerosis.